2010
DOI: 10.1016/j.techfore.2009.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Cross-country diffusion of photovoltaic systems: Modelling choices and forecasts for national adoption patterns

Abstract: In this paper we propose an innovation diffusion framework to analyze and forecast national adoption patterns of photovoltaic installed capacity. Comparisons are proposed among several countries in order to highlight the effect of incentive policies. Results seem to suggest that the current available PV technology is going to complete its life cycle and that new solutions for solar energy should become available in the short term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(67 citation statements)
references
References 14 publications
7
57
1
Order By: Relevance
“…Despite their identified shortcomings, diffusion of innovation models have been used to analyse renewable energy technology diffusion, deriving p and q from empirical data to predict diffusion [11]. In the impact assessment produced as part of the UK feed-in tariff policy design, an S-curve model is used to predict adoption due to the incentives proposed [12,Figure 4].…”
Section: Technology Adoptionmentioning
confidence: 99%
“…Despite their identified shortcomings, diffusion of innovation models have been used to analyse renewable energy technology diffusion, deriving p and q from empirical data to predict diffusion [11]. In the impact assessment produced as part of the UK feed-in tariff policy design, an S-curve model is used to predict adoption due to the incentives proposed [12,Figure 4].…”
Section: Technology Adoptionmentioning
confidence: 99%
“…Studies have shown that the prevalence of a new technology has a significant effect on the rate of uptake [3,4,18,25]. Moreover, the results of our variance tests indicate the best features for segmenting customers into categories with different likelihoods of adoption.…”
Section: Adoption Modelmentioning
confidence: 62%
“…The latter is important as financial savings could be the underlying driver of adoption and simply correlated with income. In addition, prior attempts to build a diffusion based adoption model have not factored in the financial savings when fitting model parameters with historical data [5,18,4,21].…”
Section: Introductionmentioning
confidence: 99%
“…A comparable study by Guidolin et al also found that positive government policies in form of incentives and subsidies positively influenced PV N. Opiyo diffusions across 11 countries [9]. Wustenhagen found that positive government policies, especially feed-in-tariffs (FiT), were largely responsible for the boom in PV installation in Germany [10].…”
Section: Impacts Of Subsidies On Pv Diffusionsmentioning
confidence: 89%